In situ optical emission spectroscopic investigations during arc plasma synthesis of iron oxide nanoparticles by thermal plasma - Banerjee, Indrani; Joshi, N. K.; Sahasrabudhe, S. N.; Kulkarni, Naveen V.; Karmakar, Soumen; Pasricha, R.; Ghorui, S.; Tak, Atul K.; Murthy, Shri P. S. S.; Bhoraskar, S. V.; Das, A. K. (IEEE Transactions on Plasma Science, 2006)
Investigations using in situ precursor spectroscopy during the growth of nanoparticles of iron oxide by thermal plasma induced gas phase condensation method have been shown to be useful for correlating the size of nanoparticles with existing plasma parameters. The relative abundance of ionized Fe species inside the plasma plume is seen to directly establish the relation between particle size, arc current, arc length, and ambient pressure of the reacting oxygen gas. The argon plasma from a transferred arc reactor is made to impinge on the anode that is allowed to vaporize and react with oxygen. The spectral line profiles of both Ar and Fe along the plasma column during the synthesis of nanoparticles have been proved to be useful in understanding the growth mechanism. Band intensities of FeO molecular states indicated the inverse relation with particle sizes that have been correlated to the two competitive processes in which energy is released, namely: 1) one involving the radiative transition and 2) the other that of the growth by coagulation. Atomic Boltzmann plots are used for estimating the temperatures of the zones, whereas particle sizes have been inferred using transmission electron microscopic measurements.
Keywords: plasma arc device; plasma-materials processing applications; spectroscopy